Nigella sativa supplementation improves cardiometabolic indicators in population with prediabetes and type 2 diabetes mellitus: A systematic review and meta-analysis of randomized controlled trials - Saadati, Saeede; Naseri, Kaveh; Asbaghi, Omid; Abhari, Khadijeh; Zhang, Pangzhen; Li, Hua-Bin; Gan, Ren-You (Frontiers in Nutrition, 2022)
Objective: Nigella sativa (N. sativa) from the family Ranunculaceae has medicinal properties. Previous studies have reported promising findings showing that N. sativa may benefit cardiometabolic health; however, current evidence on its effects on type 2 diabetes mellitus (T2DM) is still unclear. Hence, we conducted a systematic review and meta-analysis to assess the efficacy of N. sativa on cardiometabolic parameters in population with prediabetes and T2DM. Methods: PubMed/Medline, ISI Web of Science, Scopus, and Cochrane library were systematically searched up to June 20, 2022. Meta-analyses using random-effects models were used. Results: Eleven randomized controlled trials (RCTs) were included in the meta-analysis. N. sativa intervention resulted in significant changes in fasting plasma glucose (FPG), hemoglobin A1c (HbA1c), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), c-reactive protein (CRP), and malondialdehyde (MDA), without any changes in glucose levels after oral glucose tolerance test (OGTT), fasting insulin, homeostatic model assessment of insulin resistance (HOMA-IR), triglyceride, high-density lipoprotein cholesterol (HDL-C), and body mass index (BMI) when compared with the control group. In subgroup analyses, N. sativa supplementation enhanced serum levels of HDL-C in subjects with baseline HDL-C lower than 40 mg/dL. Furthermore, HOMA-IR and BMI values decreased in the N. sativa-supplemented group compared with the control group, when the length of follow-up was more than eight weeks and the dose was more than one g/day for N. sativa supplementation, respectively. Conclusion: Our findings indicate that N. sativa supplementation may effectively improve cardiometabolic profiles in individuals with prediabetes and T2DM.